Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1140/epjst/e2017-70059-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen vacancies on two-dimensional electron systems at SrTiO3-based interfaces and surfaces

Abstract: Abstract. The insulator SrTiO 3 can host high-mobility twodimensional electron systems on its surfaces and at interfaces with other oxides. While for the bare surface a two-dimensional electron system can only be induced by oxygen vacancies, it is believed that the metallicity of heterostructure interfaces as in LaAlO 3/SrTiO3 is caused by other mechanisms related to the polar discontinuity at the interface. Based on calculations using density functional and dynamical mean-field theory as well as on experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 105 publications
3
24
0
Order By: Relevance
“…These states determine the interfacial ferromagnetism of OD-LAO/STO [23,24]. This theoretical picture of the dichotomic electron system formed at the OD-LAO/STO interface [25][26][27][28] has recently been experimentally confirmed by resonant photoemission (ResPE) experiments [29]. The coexistence of the two radically different MES and IGS electron subsystems much enriches the physics of the OD-LAO/STO interfaces compared to the stoichiometric ones.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…These states determine the interfacial ferromagnetism of OD-LAO/STO [23,24]. This theoretical picture of the dichotomic electron system formed at the OD-LAO/STO interface [25][26][27][28] has recently been experimentally confirmed by resonant photoemission (ResPE) experiments [29]. The coexistence of the two radically different MES and IGS electron subsystems much enriches the physics of the OD-LAO/STO interfaces compared to the stoichiometric ones.…”
Section: Introductionmentioning
confidence: 76%
“…This observation still has to be fully understood, although a few theoretical works have demonstrated that properties of the V O s depend on their concentration regime [21,46]. An ARPES study of the EPS at the bare STO(100) and (111) surfaces [16,28] has presented evidence that this phenomenon is driven by clustering of V O s. Indeed, local-density approximation (LDA) +U calculations on bare STO surfaces [21,46] suggest that the electron distribution between the MES and IGSs may depend on particular configurations of V O s; while isolated V O s on the surface tend to donate both released electrons into the MES, their cluster configurations favor even distribution. We note that the intensity evolution of the ARPES spectral structures under x-ray irradiation is accompanied by their energy shifts (see Supplemental Material 1 [35]).…”
Section: A X-ray Irradiation Dynamicsmentioning
confidence: 99%
“…Here we considered only spin and charge neutral vacancies; however, there is an interesting physics underlying F centers (anionic vacancies) [50]. With the advent of modern thinfilm technology, targeted manipulation and control of defects, in particular at their two-dimensional surfaces and interfaces, has become possible [51]. Moreover, theoretical investigation of defects is critical to understanding the electronic properties of semiconducting compounds [52].…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation seems to be present in other transition metal oxides like SrTiO 3 83 and its interfaces. 84,85 Furthermore, extrinsic loss that can be large for plasmonic satellites 86 , is not included in our calculations. We propose that the difference in spectral weight between the photoemssion experiments and our ab initio results in the inset of Fig.…”
Section: Spectral Functionsmentioning
confidence: 99%